STRATEGI RETENSI KARYAWAN DALAM PENURUNAN ANGKA TURNOVER - Agustinus Doedyk Setiyawan; Roro Kusumaningrum (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2018)
Employee retention that is not done well in a company will result in high turnover rates. And the company's losses can not be avoided again when the turnover rate is very high because it will also affect the additional costs of recruitment and training of new employees, the decline of certain unit performance, and also the loss of knowledge and skills capital that has been given by the company. Regarding high turnover rates in a company, the Personnel Unit is required to be able to manage human resources well which is able to reduce the turnover rate. There are five types of employee retention strategies, namely compensation, fulfillment of employee expectations, employee induction, attention to employees' families, and employee training and development.